PELAKSANAAN PENETAPAN HARGA JUAL DALAM JUAL BELI TANAH OLEH BADAN KEUANGAN DAERAH KOTA SINGKAWANG - NIM. A1012191043, SINDY PRATAMA PUTRI (Fakultas Hukum Universitas Tanjungpura, 2023)
Abstrac Land is a natural resource that is important for human survival, but over time land is also bought and sold. Buying and selling is a process of exchanging goods between one party and another. In land sale and purchase transactions, the purchaser's tax is determined based on the Land and Building Rights Acquisition Fee, which is a tax imposed on the acquisition of land and/or building rights. Meanwhile, income tax is a tax imposed according to the taxpayer's income earned in a given year. With this determination, the selling price in each region is different and the selling price is higher than the price agreed upon by the parties or taxpayers, as a result, taxpayers who sell their land at low prices object to the selling price set by the Regional Financial Agency.The formulation of the problem in this research is